Self-powered action in metal-semiconductor-metal ultraviolet photodetectors based on AlGaN/GaN high electron mobility transistor structures on different substrates - Razeen, Ahmed S. (2024)
AlGaN/GaN based metal-semiconductor-metal (MSM) ultraviolet photodetectors (UV PDs) are highly in demand for several applications that require thermal and mechanical stability, and strength to handle different environmental conditions. However, the electro-optic performance of these devices is very low in self-powered operation mode, which limits their potential to be implemented for practical applications. In this work, AlGaN/GaN HEMT-based MSM UV PDs were successfully fabricated with symmetric metal dimensions and different finger counts on the two sides of the interdigitated metal configuration. The PDs achieved responsivity of 2.2 A/W and detectivity of 1.3×1011 Jones at zero applied voltage. The devices also showed dark current as low as 16 pA and photo-to-dark current ratio of ∼ 103 under self-powered operation, with fast and stable response speed. This high-performance operation is attributed to the high crystal quality and low defect density of the base layer structure. The results support the potential of HEMT-fabrication based self-powered UV photodetector devices for portable power electronic applications.